Development of E-Modules to Improve Higher-Order Thinking Skills in Basic Accounting Subjects at Vocational Schools - Jayanti, Fitria; Suarman; Syhaza, Almasdi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This paper documents learning resources in electronic modules created to improve or explore students' Higher-Order Thinking Skills (HOTS) that are valid, practical, and effective. The research method used is Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The feasibility of the E-Module which was developed based on the results of module expert validation obtained 97.7% with very valid product criteria or suitable for use. Based on material expert validation, 94.5% was obtained with the valid or convenient product criteria. Based on the results of implementation in the field by basic accounting subject educators and students, the practicality of the E-Module developed received an assessment of the teacher's response with an average percentage score of 88.28% with convenient criteria and student responses with an average percentage score of 87.25% with efficient criteria. Furthermore, the E-Module developed was proven effective based on the results of the T-test and N-test gain analysis score is 0.842, which is in the high category. Therefore, this E-Module is effective in improving students' high-level thinking abilities.